Effect of drugs on cholesterol crystallization in an artificial bile model and relation of this effect to drug binding to albumin - Smídková, Markéta; Spundová, Marcela; Marecek, Zdenek; Entlicher, Gustav (Fundamental & clinical pharmacology, 2003)
Substances that can affect the crystallization of cholesterol from human bile and consequently the gallstone formation have been given considerable attention. We improved the model system for testing cholesterol crystallization-affecting activity (promoting or inhibiting) of substances and used it for some drugs that are excreted into bile. Besides other factors natural lipid-protein complexes isolated from the native human bile have been shown to be responsible for nucleation and fast crystal growth in cholesterol supersaturated model bile. Artificial lipid-protein complex of taurolithocholate, human serum albumin and Ca2+ (TLTC-HSA-Ca2+) exhibited a lower crystallization activity than both the artificial lipid-protein complexes of taurodeoxycholate, human serum albumin and Ca2+ and the lipid-protein complex isolated from native human bile. The model bile supplemented with this artificial lipid-protein complex (TLTC-HSA-Ca2+) formed a convenient system for testing of various substances (drugs) for their crystallization-affecting activity. From the 20 tested drugs, which could occur at least in small amounts in human bile, the highest crystallization-promoting activity was found for complexes with ampicillin, butorphanol and colchicine. Complexes with tetracycline, thioridazine and doxycycline were the strongest inhibitors. The drugs, which had some effect on cholesterol crystallization, affected somehow the artificial lipid-albumin complex by displacing its components. Interactions of different drugs with HSA and its artificial complexes with the conjugated bile salt and Ca2+ ions were followed by absorption spectroscopy to observe displacement interactions. On the basis of these experiments we could classify drugs into four groups which differ by their effects on spectral characteristics of complexes.
Keywords: kyselina taurochenodeoxycholová; Calcium; Protein Binding; Crystallization; Models, Biological; chemické modely; sérový albumin; Taurochenodeoxycholic Acid; biologické modely; vápník; Bile; Cholesterol; léčivé přípravky; vazba proteinů; kyselina taurodeoxycholová; Taurolithocholic Acid; Serum Albumin; žluč; Taurodeoxycholic Acid; krystalizace; kyselina taurolithocholová; Pharmaceutical Preparations; cholesterol; Models, Chemical